Bovine Viral Diarrhea Virus in Cattle From Mexico: Current Status - Gomez-Romero, Ninnet; Ridpath, Julia F.; Basurto-Alcantara, Francisco Javier; Verdugo-Rodriguez, Antonio (Frontiers in Veterinary Science, 2021)
Bovine viral diarrhea (BVD) is an infectious disease, globally-distributed, caused by bovine Pestiviruses, endemic of cattle and other ruminant populations. BVD leads to significant economic losses to the cattle industry due to the wide range of clinical manifestations, including respiratory and gastrointestinal diseases and reproductive disorders. Within the Pestivirus genus of the family Flaviviridae three viral species are associated with BVD; Pestivirus A (Bovine viral diarrhea virus 1, BVDV-1), Pestivirus B (Bovine viral diarrhea virus 2, BVDV-2), and Pestivirus H (HoBi-like pestivirus, atypical ruminant pestivirus). These species are subdivided into subgenotypes based on phylogenetic analysis. The extensive genetic diversity of BVDV has been reported for several countries, where the incidence and genetic variation are more developed in Europe than in the Americas. The first report of BVDV in Mexico was in 1975; this study revealed seropositivity of 75% in cows with a clinical history of infertility, abortions, and respiratory disease. Other studies have demonstrated the presence of antibodies against BVDV with a seroprevalence ranging from 7.4 to 100%. Recently, endemic BVDV strains affecting cattle populations started to be analyzed, providing evidence of the BVDV diversity in several states of the country, revealing that at least four subgenotypes (BVDV-1a, 1b, 1c, and 2a) are circulating in animal populations in Mexico. Little information regarding BVD epidemiological current status in Mexico is available. This review summarizes available information regarding the prevalence and genetic diversity viruses associated with BVD in cattle from Mexico.